Bioadhesive and biodissolvable hydrogels consisting of water‐swellable poly(acrylic acid)/poly(vinylpyrrolidone) complexes. Issue 2 (8th May 2019) - Ito, Tomoko; Otani, Naoki; Fujii, Kazuya; Mori, Kentaro; Eriguchi, Masazumi; Koyama, Yoshiyuki
Abstract: Films that can form bioadhesive hydrogels on wet biotissues absorbing blood or body fluids are useful for medical devices such as hemostats, adhesion barriers, wound dressings, and drug release devices. We focused on a hydrogen‐bonding polymer complex consisting of poly(acrylic acid) (PAA) and poly(vinylpyrrolidone) (PVP). PAA is known as a tissue‐adhesive polymer. However, simple mixing of aqueous PAA and PVP solutions resulted in the formation of an insoluble nonadhesive precipitate. We developed a novel solid/solution interface complexation method to afford a PAA/PVP complex that forms a strongly bioadhesive hydrogel with low cytotoxicity. The complex hydrogel can be slowly dissociated and dissolved in the body. The formation of the complexes as well as their swelling and degradation behavior depended strongly on the molecular weights and cross‐linking densities of the component polymers. When the complex film was applied to a clipped incised jugular vein of a rat, it immediately formed a hydrogel and closed the incision. After removal of the clip, blood flowed through the vessel without any leakage. Application of the complex film to the surface of an incised mouse liver resulted in firm adhesion and the hemorrhage was effectively stopped. Such bioadhesive and biodissolvable materials consisting of low‐toxicity synthetic polymers have high potential for implantable medical devices.